The Impact of Teaching Methodologies and Syllabus on Student Learning in Private and Public Schools in Chakwal - Zaib Un Nissa; Dr. Abid Ghafoor Chaudhry (Journal of Peace, Development and Communication, 2024)
This research was conducted to explore the impact of teaching methodologies and syllabus on student learning in private and public schools in Chakwal, Pakistan. Private schools have smaller class sizes, better infrastructure, and more modern teaching methods as compared to their public schools, which are usually constrained by larger class sizes and limited resources. : Two schools were selected by the researcher by applying probability sampling technique through simple random. The sample size of 105 respondents (teachers and student) had been taken through purposive sampling technique. This study employs a mixed-methods approach, combining surveys, case studies and interviews to gather data from both teachers and students across a representative sample of schools from both sectors. Ultimately, this research objects to contribute in the ongoing educational equity and effectiveness by suggesting relationship between teaching methodologies, syllabus design, and student learning outcomes in different school sectors in Chakwal. These findings to foster improvements in educational practices and outcomes between both private and public schools in this region especially in policy making and students learning.